Validating the factor structure of school principals’ transformational leadership scale in Vietnam - Tran, Van Dat; Trang Bui, Le Diem; Le, Minh Tuan Lam; Huynh, Thi Cam; Nguyen, Huynh Thuan (Institute of Advanced Engineering and Science, 2025)
Recently, there has been a growing emphasis on investigating the factor structure of the transformational leadership style due to its significant impact on teachers’ outcomes and school-related factors such as organizational citizenship behaviors, organizational commitment, work dedication, creativity, and school innovation. However, the existing literature reveals a lack of studies focusing on the dimensions of transformational leadership style in Vietnam. The present study, therefore, aims to validate the factor structure of the 20-item transformational leadership scale, derived from the 45-item multifactor leadership questionnaire (MLQ), which was translated into Vietnamese and administered to 375 high school teachers. The results of both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) confirmed the suitability of the original MLQ’s five-factor structure of transformational leadership, which includes idealized influence attributed (IIa), idealized influence behavioral (IIb), inspirational motivation (IM), intellectual stimulation (IS), and individualized consideration (IC). The fit indices of the model (χ2/df=1.57, p=0.000, TLI=0.91, CFI=0.90, and RMSEA=0.067), and Cronbach’s alpha values of all subfactors (α≥0.73) were satisfactory. The findings recommend that high schools might utilize the MLQ in evaluating teachers’ views of transformational leadership within the context of Vietnamese high school education to improve the leadership practices of principals.